ENERGY SELF-SUFFIENCY IN REALIZING SUSTAINABLE DEVELOPMENT IN INDONESIA : BETWEEN REALISTIC AND IMAGINARY GOALS - Heppi Syofya; Deni Gunawan; Suseno Hendratmoko; Lisbet Situmorang; Ridwan Sya’rani (Adisam Publisher, 2024)
One of the hot topics of discussion at the moment is the government's policy of continuing to develop renewable energy alternatives. Energy Self-Sufficiency in Realizing Sustainable Development in Indonesia. This research aims to analyze the possibility of an Energy Self-Sufficiency development plan in realizing sustainable development in Indonesia, whether it is implemented realistically or not. If it is realistic then it can be categorized as a plan and if it is not realistic then the plan can be categorized as mere discourse. This research is qualitative research with a descriptive approach. The data used in this research is secondary data which researchers obtained from trusted websites, scientific journals, books and other trusted sources that are credible and commonly used in research. The analysis technique in this research uses descriptive analysis techniques to describe whether Energy Self-Sufficiency in realizing Sustainable Development in Indonesia is realistic or not. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions.